Activity dynamics and behavioral correlates of CA3 and CA1 hippocampal pyramidal neurons - Mizuseki, Kenji; Royer, Sebastien; Diba, Kamran; Buzsaki, Gyoergy (WILEY, 2012)
The CA3 and CA1 pyramidal neurons are the major principal cell types of the hippocampus proper. The strongly recurrent collateral system of CA3 cells and the largely parallel-organized CA1 neurons suggest that these regions perform distinct computations. However, a comprehensive comparison between CA1 and CA3 pyramidal cells in terms of firing properties, network dynamics, and behavioral correlations is sparse in the intact animal. We performed large-scale recordings in the dorsal hippocampus of rats to quantify the similarities and differences between CA1 (n similar to 3,600) and CA3 (n similar to 2,200) pyramidal cells during sleep and exploration in multiple environments. CA1 and CA3 neurons differed significantly in firing rates, spike burst propensity, spike entrainment by the theta rhythm, and other aspects of spiking dynamics in a brain state-dependent manner. A smaller proportion of CA3 than CA1 cells displayed prominent place fields, but place fields of CA3 neurons were more compact, more stable, and carried more spatial information per spike than those of CA1 pyramidal cells. Several other features of the two cell types were specific to the testing environment. CA3 neurons showed less pronounced phase precession and a weaker position versus spike-phase relationship than CA1 cells. Our findings suggest that these distinct activity dynamics of CA1 and CA3 pyramidal cells support their distinct computational roles. (C) 2012 Wiley Periodicals, Inc.
Keywords: SODIUM-CHANNEL INACTIVATION; THETA PHASE PRECESSION; SINGLE UNIT-ACTIVITY; PLACE CELLS; SPATIAL REPRESENTATION; DENDRITIC SPIKES; DISTINCT REPRESENTATIONS; SYNAPTIC PLASTICITY; PATH-INTEGRATION; BURST GENERATION